Ascertaining of temporomandibular disorders (TMD) with clinical and instrumental methods in the group of young adults - Sójka, Anna; Huber, Juliusz; Kaczmarek, Elżbieta; Hędzelek, Wiesław (Journal of Medical Science, 2015)
Introduction. During the diagnostic process, the clinical examination of the masticatory system combined with jaw movement measurements can indicate the presence of temporomandibular disorders (TMD) symptoms. Aim. The aim of the present study was to determine the presence of clinical symptoms of TMD in a group of subjects aged 19–27 years and to analyze the measurable parameters obtained from examinations carried out using the Arcus®digma.Material and methods. Eighty four dentate subjects from 19 to 27 years were recruited from students. Objective signs were studied with Helkimo Anamnetic index (Ai) and the subjective symptoms were evaluated with Gsellmann’s Occlusal Index (OI). Functional examination of the masticatory system was performed using Helkimo Clinical Dysfunction index (Di). Pain symptoms were determined in clinical examination using visual analogue scale. Software of Arcus®digma allowed the analysis of Bennett’s angle and movement, the horizontal condylar inclination, retrusion, anterior guidance and Immediate Side Shift.Results. Occasional pain occurred in 39% of students and correlated with increase of OI index, subjects with higher Di displayed higher values of OI. Comparison of Bennett’s angle values for the right and left TMJ showed the significant asymmetry, similarly like the values of Bennett’s movement and retrusion between the left and right TMJ.Conclusions. Bennett’s angle, Bennett’s movement and retrusion were significant parameters in instrumental evaluation of TMD symptoms. The questionnaire and clinical examination supplemented with axiographic recordings revealed the presence of TMD symptoms in students who were not fully aware of TMJ disorders.